The dynamics of specialist development banking : the case of the agriculture development bank of Trinidad and Tobago - Birchwood, Anthony (CEPAL SantiagoCL, 2007)
Examines the evolution and performance of development banking in Trinidad and Tobago, focussing in particular on the Agriculture Development Bank of Trinidad and Tobago (ADB). Explores the strategic focus of ADB, highlights the institutional framework and examines the governance and administrative scheme of the bank. Explores issues regarding ADB's ability to collect funds, and its autonomy. Suggests ways of strengthening financial intermediation by the bank and also ways by which specialist development banks can increase their viability.